Smartphone Application Technology In Control Robot In Search Focal Point (Pengaplikasian Teknologi Smartphone Dalam Pengontrolan Robot Dalam Pencarian Titik Api) - Nanda Tommy Wirawan (Universitas Putra Indonesia YPTK Padang, 2020)
Smartphone Technology Utilization in this research aims to control the robot in finding hotspots so that we can know the point of fire from any angle. And the robot can be set automatically in the search for hotspots without having to be controlled. When the robots find fire robot will notify to the Smartphone that fire was found. For communication lines and Smartphone Robot uses HC-05 Bluetooth.This study aims to facilitate human find fire in the room is cramped and difficult to pass. So prevention was quickly taken not to spread to a larger one. In the results of this study indicate that the robot is made to function properly and can be expanded to a larger scale.